Peran Seni dalam Pendidikan Anak untuk Mengasah Kreativitas - Aviska, Shella (Maliki Interdisciplinary Journal, 2025)
Art education plays a crucial role in developing children's creativity. The approach to art education includes teaching technical skills and using art as a medium for general learning. Art enables children to express ideas, nurture imagination, and build social and emotional skills. However, the focus of art education often shifts toward achieving recognition instead of the learning process. Ki Hadjar Dewantara's "trisakti jiwa" principle emphasizes freedom, creativity, and balance in learning, enabling children to enhance creativity and independence. Art education that supports free exploration encourages children to become innovative, critical, and confident individuals. Art is not just a means of entertainment but also a means of holistic individual development. With a process-oriented approach, art helps children learn without pressure, creating a generation that is creative, innovative and appreciates culture.